2014
DOI: 10.1124/mol.113.089433
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Arsenical Darinaparsin Is Transported by Cystine Importing Systems

Abstract: Darinaparsin (Dar; ZIO-101; S-dimethylarsino-glutathione) is a promising novel organic arsenical currently undergoing clinical studies in various malignancies. Dar consists of dimethylarsenic conjugated to glutathione (GSH). Dar induces more intracellular arsenic accumulation and more cell death than the FDAapproved arsenic trioxide (ATO) in vitro, but exhibits less systemic toxicity. Here, we propose a mechanism for Dar import that might explain these characteristics. Structural analysis of Dar suggests a put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Tian et al reported no significant side effect of darinaparsin on fast-cycling cell populations such as those in the BM or intestine (43). Darinaparsin is currently being tested in phase 2 clinical trials for solid tumors and hematopoietic malignancies; however, its molecular mechanism of action has not been fully elucidated (51). It has been reported that ATO antagonizes both GLI1 and GLI2 (41,42), and a very recent report also suggests that darinaparsin might reduce GLI2 protein levels in prostate tumor-initiating cells (44).…”
Section: The Novel Organic Arsenic Darinaparsin Reduces Gli1 and Gli2mentioning
confidence: 99%
“…Tian et al reported no significant side effect of darinaparsin on fast-cycling cell populations such as those in the BM or intestine (43). Darinaparsin is currently being tested in phase 2 clinical trials for solid tumors and hematopoietic malignancies; however, its molecular mechanism of action has not been fully elucidated (51). It has been reported that ATO antagonizes both GLI1 and GLI2 (41,42), and a very recent report also suggests that darinaparsin might reduce GLI2 protein levels in prostate tumor-initiating cells (44).…”
Section: The Novel Organic Arsenic Darinaparsin Reduces Gli1 and Gli2mentioning
confidence: 99%
“…For both drugs, extracellular γGT activity is an essential and limiting step in their activation into membrane permeable compounds (Dilda et al, 2008; Garnier et al, 2014). Indeed, it has recently been demonstrated that tumor γGT could be used for therapeutic delivery (Ramsay et al, 2014).…”
Section: Glutathione S-derivatives Activated By γGt and Peptidasesmentioning
confidence: 99%
“…The newly formed cysteinylglycine S -conjugates are further processed by dipeptidases/aminopeptidases to remove the glycyl group and produce cysteine S -conjugates. These compounds then re-enter the cell via various transporters including organic anion transport polypeptides and cystine/cysteine importers (Hinchman et al, 1998; Budy et al, 2006; Dilda et al, 2008, 2009; Garnier et al, 2014). In the cytosol, N -acetyl transferases create mercapturic acid versions of the xenobiotics which are generally more polar and more water soluble than the parental compound.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other arsenicals with antitumor activity and with less toxicity and oral availability have been sought. Darinaparsin is an organic arsenic (S-dimethylarsino-glutathione; Z-101) made by conjugating dimethylarsenic to glutathione (4,5). Screening of the NCI-60 panel of cells indicated that Ic-50 concentrations with darinaparsin ranged from 0.02 to 7.3 mmol/L.…”
Section: Introductionmentioning
confidence: 99%